Penerapan Model Berpikir Induktif (Inductive Thinking Model) untuk Meningkatkan Hasil Belajar Kognitif IPA Biologi Siswa - Irwansah Irwansah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
This study aims to improve the learning outcomes of biology science learning in MTs students. Darul Aminin NW Aikmual, Central Lombok Regency through inductive thinking model (inductive thinking). The subjects in this study were students of class VII MTs. Darul Aminin NW Aikmual, Central Lombok Regency. The instruments used in this study were observation sheets to collect data about teacher and student activities during the learning process, and student cognitive learning outcomes test sheets. This research is a Classroom Action Research (PTK) with the following steps: planning, implementing the action, observing, and reflecting. The approach used to study the problem is a qualitative approach and a quantitative approach. Data collection techniques used are: observation, interviews, tests, and documentation. Based on the results of the study, it was found that, in the first cycle the completeness of student learning outcomes obtained a percentage of completeness of 54.28% belonging to the fairly active category. Whereas in cycle II, the percentage of completeness is 88.57% which is classified as active category. This shows an increase in biology science learning outcomes in class VII MTs students. Darul Aminin NW Aikmual, Central Lombok Regency.